Multifunctional Response of Piezoelectric Sodium Potassium Niobate (NKN)-Toughened Hydroxyapatite-Based Biocomposites - Verma, A.S.; Sharma, A.; Kumar, A.; Mukhopadhyay, A.; Kumar, D.; Dubey, A.K. (American Chemical Society, 2020)
In this study, hydroxyapatite (HA)-sodium potassium niobate (NKN) composites with varying concentrations of NKN (10, 20, and 30 wt %) were optimally developed at 1075 °C for 2 h. Detailed microstructural analyses have been performed by means of scanning and transmission electron microscopy. The maximum fracture toughness, hardness, and compressive and flexural strengths were obtained to be ∼209, ∼93, ∼112, and ∼88%, respectively, for the HA-30 wt % NKN composite compared to monolithic HA. The antibacterial tests revealed the significant reduction in bacterial viability on poled (@ 20 kV for 30 min at 500 °C) HA-NKN composite samples while cultured with Staphylococcus aureus and Escherichia coli bacteria. The cytocompatibility tests revealed the significantly enhanced MG63 cell proliferation for electrical stimulation-treated negatively charged HA and H30N composite samples. © 2020 American Chemical Society.
Keywords: hydroxyapatite; sodium potassium niobate (NKN); mechanical properties; polarization; antibacterial behavior